2007
DOI: 10.4028/www.scientific.net/ssp.130.155
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of β Phase in WE54 Magnesium Alloy

Abstract: Precipitation hardened magnesium-rare earth alloys offer attractive properties for the aerospace and racing automotive industries. The most successful magnesium alloys developed to date have been those based on the Mg-Y-Nd system identified as WE54 (Mg-5.0wt%Y-4.1wt%RE-0.5wt%Zr) and WE43 (Mg-4.0wt%Y-3.3wt%RE-0.5wt%Zr), where RE represents neodymium-rich rare earth elements. Precipitations sequence in WE-system alloys involved the formation of phases designated β”, β’, β1 and β depending on the ageing temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Magnesium alloys of the Mg-RE-Zr group in as-cast condition are characterized by a structure of α-Mg solid solution with precipitates of intermetallic phases along grain boundaries and within the solid solution grains. Mg 41 Nd 5 and Mg 24 Y 5 [6] phases are observed in the WE43 alloy, Mg 2 Y, Mg 24 Y 5 i Mg 12 YNd [7] in the WE54 alloy and Mg 3 (Nd,Gd) type phase has been found in the EV31A alloy. The volume fraction of the intermetallic phases is similar in all alloys and is equal about 6% [9].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium alloys of the Mg-RE-Zr group in as-cast condition are characterized by a structure of α-Mg solid solution with precipitates of intermetallic phases along grain boundaries and within the solid solution grains. Mg 41 Nd 5 and Mg 24 Y 5 [6] phases are observed in the WE43 alloy, Mg 2 Y, Mg 24 Y 5 i Mg 12 YNd [7] in the WE54 alloy and Mg 3 (Nd,Gd) type phase has been found in the EV31A alloy. The volume fraction of the intermetallic phases is similar in all alloys and is equal about 6% [9].…”
Section: Discussionmentioning
confidence: 99%
“…The coarse eutectic structures located at the grain boundaries (shown by arrows B) are Nd-rich phases as shown in Table 2. It is reported that the coarse phases distributed along the grain boundaries in cast Mg-Nd-Y alloy are considered as Mg 41 Nd 5 [34,35] or Mg 12 Nd [9,27,36]. Since the atomic ratio of Mg and Nd is higher than 12, the coarse phase B is possibly Mg 12 Nd phase with oversaturated Mg atoms.…”
Section: Microstructurementioning
confidence: 98%
“…4(d) shows the high magnification image of rectangular particle, and EDS analysis shows that it is Y-rich phase. The rectangular shaped particle was represented as Mg 24 Y 5 in a lot of investigations [27,34,36]. According to the chemical composition and morphology, the rectangular particles exhibit in BM and FSP samples are Mg 24 Y 5 .…”
Section: Microstructurementioning
confidence: 99%
“…On the other hand, inferior heat stability limited the field of use of magnesium. Nowadays, some magnesium alloys may withstand the temperatures up to 300°C without significant loss of mechanical properties [2]. Recently, magnesium was discussed also as a material for biodegradable implants due to its biocompatibility and degradation performance.…”
Section: Introductionmentioning
confidence: 99%